Central blood pressure estimation in type 1 diabetes: impact and implications of peripheral calibration method. Issue 1 (7th January 2023) - Helleputte, Simon; Spronck, Bart; Sharman, James E.; Van Bortel, Luc; Segers, Patrick; Calders, Patrick; Lapauw, Bruno; De Backer, Tine
Abstract : Objective: Peripheral blood pressure (BP) waveforms are used for noninvasive central BP estimation. Central BP could assist in cardiovascular risk assessment in patients with type 1 diabetes mellitus (T1DM). However, correct calibration of peripheral BP waveforms is important to accurately estimate central BP. We examined differences in central BP estimated by radial artery tonometry depending on which brachial BP (SBP/DBP vs. MAP/DBP) is used for calibration of the radial waveforms, for the first time in T1DM. Methods: A cross-sectional study in T1DM patients without known cardiovascular disease. Radial artery BP waveforms were acquired using applanation tonometry ( SphygmoCor ) for the estimation of central SBP, central pulse pressure (PP) and central augmentation pressure, using either brachial SBP/DBP or MAP/DBP for the calibration of the radial pressure waveforms. Results: Fifty-four patients (age: 46 ± 9.5 years; T1DM duration: 27 ± 8.8 years) were evaluated. Central BP parameters were significantly higher when brachial MAP/DBP-calibration was used compared with brachial SBP/DBP-calibration (7.5 ± 5.04, 7.5 ± 5.04 and 1.5 ± 1.36 mmHg higher central SBP, central PP and central augmentation pressure, respectively, P  < 0.001). Conclusion: In patients with T1DM, there are significant differences in central BP values estimated with radial artery tonometry, depending on the method used for calibration of the radial waveforms. Brachial MAP/DBP-calibration resulted in consistently higher central BP as compared to using brachial SBP/DBP, leading to patient re-stratification. Hence, the accuracy of noninvasive estimation of central BP by radial tonometry is dependent on calibration approach, and this problem must be resolved in validation studies using an invasive reference standard to determine which method best estimates true central BP.